Implementasi Konsep Qardh dalam Penggunaan Kartu Kredit Syariah - Rohmah, Rodyah Awallul; Khusnudin, Khusnudin (Jurnal Iqtisaduna, 2024)
Islamic financial practices continue to be adapted to meet the challenges of the modern world. One modernization of the qardh principle can be seen in the application of the use of Islamic credit cards. Islamic credit cards are designed to avoid the element of usury in the financing structure. The purpose of this study is to examine more deeply about how the concept of qardh, social and moral implications in an increasingly complex global financial system. This qualitative research uses a secondary review approach that focuses on the theoretical-normative study of the concept of qardh in modern Islamic credit card practices. The results of this study conclude that the concept of qardh in Islamic credit card practices has important relevance in the aspects of helping, justice, financial education and user responsibility, increasing accessibility and social justice, innovation in Islamic financing, maintaining economic stability, and building solidarity and social responsibility.